Peneguhan Identitas dan Ideologi Majelis Mujahidin Melalui Terjemah Al-Qur’an - Yahya, Mohamad (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2018)
This study focuses on Koreksi Tarjamah Harfiyah al-Qur’an Kemenag RI (QTK) by Muhammad Thalib, Amir (Leader) Majelis Mujahidin. Significance of this focus is due only Thalib who is bold and sincere against the authority of Al-Qur’an dan Terjemahnya by The Ministry of Religious Affairs of the RI. This study uses social identity theory and critical discourse analysis. The conclusion of this study says that Thalib’s interpretation or translation, Koreksi QTK and QTT, represent the social identity of Thalib and MM, as his context. Koreksi QTK (and QTT) is not merely a normative religious ritual; it is also the result of Thalib's dialectic in MM context with the socio-political context of Indonesia. Koreksi QTK (and QTT) is a self-affirming social media of Thalib and MM that attempt to illustrate illusively with a more peaceful, harmonious, anti-extremist-jihadist face. Both of these books are also a tool of the ideological campaign and political orientation of MM. The effort of delegitimizing QTK and the inauguration of QTT authority became a vital medium in the effort to sow the ideology and political orientation of MM in Nusantara context.